Managing Efficiency of Urban Road Toward Better Transport System - Debnath, Ripan; Islam, Mohammed Shariful; Rahuman, Khan Rubayet (Center for Research and Community Services ITB, 2008)
Increased trafiic volume introduces congestion on road affecting efficiency of road. Efiiciency assessment could be defined as the comparison between current status of roads in terms of road capacity, traflic volume, geometric design, etc. And standard of roads prescribed for well-functioning of roads. Afier the opening of Rupsha Bridge in Khulna of Bangladesh, the study road gains some additional trips : the trips previously used Rupsha Ferry terminal and trips from city center people make to visit the Bridge. The burden of traffics in an urban road result congestion on it and which makes necessity of studying whether the road is efficient or not to serve all its traflic flow. This study presents a methodological approach toward measuring efficiency of an urban road and also depicts when and how such measure might be required for an urban setting. This study conducts traflic volume, geometric design status and problem analysis to identify the problems making traffic congestion. Datasets of the road, comparing with the road standards, prove the road as an ineflicient road. The authors also discovered what the vehicle types responsible for such inefficiency are. They suggested with appropriate reasoning that motorized vehicles required to be eliminated from the road to have efficiency serving the residential trips and additional visitor trips on the road. The authors concluded by designing an alternative road for the eliminated motorized vehicles.